Ciberativismo, identidade política e metamorfose humana - Antunes, Mariana Serafim Xavier (2015)
This research of interdisciplinary nature is embedded in the field of critical social psychology, striving to interface with the sciences of anti-colonial knowledge, feminist activism in an environment of digital network of communication and information, and the development of political identities. Under a theoretical and methodological bias of the syntagma identity-metamorphosis-emancipation, the goal is to investigate elective affinities between autonomization processes of the human identity, and the development of a political awareness, whose emancipatory utopias reflect the production of emancipatory fragments of personal and collective extension. In this research, the focus is on the metamorphoses of collective political identities aimed at the social and feminist activism, as well as the arguments of scientific interpretation, which are updated at the light of a cyberfeminist scenario. Through narratives of life stories of three young people who produce art and feminist texts of activist content in communities and blogs on the internet, one tries to understand the discourse they make, who they are, and how they enhance conditions to make them come true. The senses they unveil lead us to the understanding of aspects of human metamorphosis, and gather evidence of emancipation fragments around their own metamorphosis conditions, heightening or reducing ethical and equitative potencialities in contemporary humanization programs